Chromophore Interaction in Xanthorhodopsin: Retinal-Dependence of Salinixanthin Binding - Imasheva, Eleonora S. (2008)
Xanthorhodopsin is a light-driven proton pump in the extremely halophilic bacterium Salinibacter ruber. Its unique feature is that besides retinal it has a carotenoid, salinixanthin, with a light harvesting function. Tight and specific binding of the carotenoid antenna is controlled by binding of the retinal. Addition of all-trans retinal to xanthorhodopsin bleached with hydroxylamine restores not only the retinal chromophore absorption band, but causes sharpening of the salinixanthin bands reflecting its rigid binding by the protein. In this report we examine the correlation of the changes in the two chromophores during bleaching and reconstitution with native all-trans retinal, artificial retinal analogues, and retinol. Bleaching and reconstitution both appear to be multi-stage processes. The carotenoid absorption changes during bleaching occurred not only uponhydrolysis of the Schiff base but continued while the retinal was leaving its binding site. In the case of reconstitution, the 13-desmethyl analogue formed the protonated Schiff base slower than retinal, and provided the opportunity to observe changes in carotenoid binding at various stages. The characteristic sharpening of the carotenoid bands, indicative of its reduced conformational heterogeneity in the binding site, occurs already when the retinal occupies the binding site but the covalent bond to Lys-227 via a Schiff base is not yet formed. This is confirmed by the results for retinol reconstitution, where the Schiff base does not form but the carotenoid exhibits its characteristic spectral change from the binding.